Design and development of a table top indoor herb or vegetable planter box - Muhammad Dzulhilmi Rohim (Nanyang Technological University, 2022)
This report aims to show the work done throughout the final year project. The objective was to design and develop a tabletop indoor herb/vegetable planter box. It has been emphasised that a benefit of gardening includes improving the quality of life. In a small urban city like Singapore, however, there are a number of factors such as the absence of a gardening culture and also the limit of space that curbs indoor gardening. Due to this, indoor gardening has been widely raved instead as an alternative, this still comes with its own set of challenges. Thus, this paper proposes a prototype design of a tabletop indoor herb/vegetable planter box in a Singaporean HDB apartment context. Studies have shown that incorporating technology can efficiently and effectively serve as a solution to the challenges faced for indoor gardening. Therefore, monitoring system which includes a micro-controller board (Arduino) and sensors such as soil moisture sensors and lights sensors will be involved in this project. They are coded and if the data captured does not meet or exceed certain threshold, message will be shown on the LCD screen to informed the users on the planter box condition.